QCM-ISA monoclonal antibody multi-serotype dengue immunosensor - Miguel, Roland Jay Atalin (2010)
Dengue is a mosquito-borne infection which in the recent years became a major public health concern. It is found in sub-tropical regions around the world particularly in Asian countries. There are four distinct serotypes that cause dengue. Recovery from infection by one provides lifelong immunity against that serotype but confers only partial and transient protection against subsequent infection by the other three. The dengue fever lasts for about seven days within the platelet count of the patient rapidly drops [19]. In this study, we propose a method for early diagnosis of viral infection. The setup utilizes Quarts Crystal Microbalance (QCM) which is highly sensitive to mass changes. The surface of the QCM is coated with monoclonal antibodies should be able to capture the antigen (the target virus) in this case. Different oscillator configurations for the QCM were tested. The stability of the oscillations was also observed while the QCM is under liquid (deionized water). It was also observed that the liquid flow rate on the crystal surface has minimal effect on its oscillation frequency. To test the setup initially, different concentrations of sucrose were run on the crystal surface. It was seen that the crystal oscillation frequency is inversely proportional to the sucrose concentration. Two methods of attaching the monoclonal antibodies on the QCM's gold surface were compared in this study. The first method uses 11-Mercaptoundecanoic Acid to create a sulfur-based binding site and the second one uses Protein-A with controlled PH to bind with the surface. After coating the QCM, it is then put into a flow cell so that an infected fluid could run over the coated surface at a flow rate. To simulate an infected human blood sera, we used cultured dengue antigen in culture media (Minimum Essentials + 1% Bovine Serum Albumin) dissolved in pH 7.2 potassium-buffered saline (PBS). The QCM setup shows a downward frequency shift in its oscillation frequency using the simulated blood sera with dissolved dengue antigens and a minimal shift without the dissolved antigens (PBS only). The negative shift implies that mass has been added to the system which also suggests that the monoclonal antibodies have captured the antigens. With this system the total time for diagnostics could be reduced to 30minutes as opposed to hours of waiting by using the traditional Polymerase-Chain Reaction (PCR). We have also shown in this study the possibility of using electrically-induced bond rupture to break the antigen-antibody bonds that have formed. This method will be useful in re-using the coated QCM. It is shown that after inducing a bond-rupture by increasing the peak-peak oscillation voltage of the crystal, the frequency of the QCM shifts positively. After bond rupture, the integrity of the coated QCM was checked by again running an infected fluid on its surface. After the second run, it was seen that the QCM still obtains a negative frequency shift with an infected fluid.